2019
DOI: 10.3847/1538-4357/ab0e7c
|View full text |Cite
|
Sign up to set email alerts
|

The 2016 June Optical and Gamma-Ray Outburst and Optical Microvariability of the Blazar 3C 454.3

Abstract: The quasar 3C454.3 underwent a uniquely-structured multi-frequency outburst in June 2016. The blazar was observed in the optical R band by several ground-based telescopes in photometric and polarimetric modes, at γ-ray frequencies by the Fermi Large Area Telescope, and at 43 GHz with the Very Long Baseline Array. The maximum flux density was observed on 2016 June 24 at both optical and γ-ray frequencies, reaching S max opt = 18.91 ± 0.08 mJy and S max γ = 22.20 ± 0.18 × 10 −6 ph cm −2 s −1 , respectively. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…This interpretation describes well what happened during the FP1 and is compatible with the shock-injet model (e.g. Marscher & Gear 1985;Valtaoja et al 1992;Fromm et al 2011;Hughes et al 2011;Weaver et al 2019). During the FP2, the spectral index is not varying as much as during the FP1 and the changes are slower.…”
Section: Cross-correlations For the Separate Flaring Periodssupporting
confidence: 85%
See 1 more Smart Citation
“…This interpretation describes well what happened during the FP1 and is compatible with the shock-injet model (e.g. Marscher & Gear 1985;Valtaoja et al 1992;Fromm et al 2011;Hughes et al 2011;Weaver et al 2019). During the FP2, the spectral index is not varying as much as during the FP1 and the changes are slower.…”
Section: Cross-correlations For the Separate Flaring Periodssupporting
confidence: 85%
“…Hence, the estimated collision between the blob B11 and the quasi-stationary component C could explain the origin of the multiwavelength flaring event in the latter. Weaver et al (2019) reported an ejection of a relativistic component K16 from the 43 GHz core ∼4 months before the flaring event of June 2016 (JD − 2450000 = 7448 ± 17.5) and traveled across until it disappeared. They interpreted that the electrons were accelerated from a back interaction with the core causing the variability.…”
Section: Cross-correlations For the Separate Flaring Periodsmentioning
confidence: 99%
“…An ANOVA test has been used to identify and characterize the optical flux density and polarization variability of the BL Mrk 421 (Fraija et al 2017) and the FSRQ 3C454.3 (Weaver et al 2019), with observed timescales of variability of ∼ 2 hr in both cases. The sampling rate of observations in these studies was on the order of several minutes between observations, for at most a few hours each night.…”
Section: Intraday Variability Of Tess Datamentioning
confidence: 99%
“…They are thought to be powered by relativistic jets of high-energy plasma flowing away from the central engine at nearly the speed of light (e.g., Lister et al 2016;Jorstad et al 2017), with trajectories closely aligned to the line of sight. The observed phenomena include ultraluminous emission (apparent luminosity as high as ∼ 10 50 erg s −1 , e.g., Abdo et al 2010aAbdo et al , 2011aGiommi et al 2012;Şentürk et al 2013), high amplitudes of variability on timescales as short as several minutes at various wavebands (e.g., H. E. S. S. Collaboration et al 2010;Jorstad et al 2013;Weaver et al 2019), and high degrees of optical linear polarization (which can exceed 40%; e.g., Smith 2016). Both theoretical work (e.g., Königl 1981;Marscher 1987) and observations (e.g., Hartman et al 1999;Jorstad et al 2001;Lister et al 2011) have found a tight connection between the high-energy and radio emission from the jets.…”
Section: Introductionmentioning
confidence: 99%
“…Diltz & Böttcher (2016) modeled the broad-band SED generated with data gathered during the 2010 flare, concluding that the one zone leptohadronic model provides merely poor fits. Interestingly, Weaver et al (2019) discovered a QPO with a characteristic period of 36 minutes, analyzing R-band optical data of the 2016 flare.…”
Section: C 279mentioning
confidence: 99%